Selecting reasonable soil moisture-maintaining measures to improve the soil physicochemical properties and achieve high yield and quality of purple garlic in the China Hexi Corridor oasis agricultural area - Pan, Xiaofan; Zhang, Hengjia; Deng, Haoliang; Yu, Shouchao; Zhou, Chenli; Li, Fuqiang (Frontiers in Plant Science, 2024)
Agricultural plastic film, as an important agricultural production material in the China Hexi Corridor oasis agricultural area, is widely used in the intensive production process of purple garlic, which plays an important role in increasing yield, improving quality, ensuring supply, etc. However, the difference in decomposition characteristics between ordinary plastic film and degradable plastic film may affect soil moisture and temperature, thereby affecting soil biochemical properties. Therefore, we conducted a study to solve this problem. Specifically, in the Minle area of the Hexi Corridor, we selected 10 moisture-maintaining measures of ordinary transparent plastic film, transparent oxo-biodegradable plastic film (50-, 80-, and 110-day induction period), ordinary black plastic film, black oxo-biodegradable plastic film (50-, 80-, and 110-day induction period), wheat straw, and aubergine-super absorbent polymers and used the traditional open field without super absorbent polymers as a control. To analyze the effects of different moisture-maintaining measures on soil quality, garlic yield and quality, and water-fertilizer productivity in purple garlic farmland, and conduct a comprehensive evaluation of moisture-maintaining measures using principal component analysis. The results showed that all the moisture-maintaining measures could increase garlic yield, improve bulb quality and water–fertilizer productivity, improve the soil hydrothermal conditions, maintain soil fertility, increase the microbial quantity, and improve enzyme activity. Overall, transparent plastic film mulching was superior to black plastic film mulching, straw mulching, and A-SAP, with 110-day transparent oxo-biodegradable plastic film mulching being the most effective, and was not significantly different from the ordinary transparent plastic film. Compared with other moisture-maintaining measures, the yield, water productivity, irrigation water productivity, and nitrogen fertilizer partial factor productivity of purple garlic were significantly increased by 13.33% to 119.77%, 13.81% to 126.77%, 13.41% to 119.95%, and 13.33% to 119.76%, respectively. Meanwhile, the contents of allicin, soluble sugar, soluble protein, crude fiber, and amino acid content were increased by 1.44% to 14.66%, 4.64% to 36.46%, 0.38% to 28.27%, 1.89% to 26.29%, and 0.38% to 3.74%, and, due to the prolongation of oxo-biodegradable plastic film induction period, the soil microbial community changes from “fungi type” to “bacterium type,” reducing the occurrence of soil diseases and improving soil quality. On the basis of the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method, the soil quality was evaluated, and the yield, quality, and water productivity of garlic were comprehensively evaluated under each moisture-maintaining measure using principal component analysis. It was determined that the best soil quality and better bulb quality as well as higher garlic yield and water productivity were obtained when using the 110-day induction period transparent oxo-biodegradable plastic film. It can be used as a more reasonable moisture-maintaining measure and technical reference for the purple garlic industry in the China Hexi Corridor oasis agricultural area, which can ensure the improvement of quality and stabilization of yield and also solve the risk of environmental pollution caused by plastic film mulching at the source.